The Molecular Bronchoscope: a tool for measurement of spatially dependent CO2 concentrations in the lungs - Ciaffoni, L; Couper, J; Richmond, G; Hancock, G; Ritchie, G (American Chemical Society, 2017)
Respiratory physicians use bronchoscopy for visual assessment of the lungs' topography and collecting tissue samples for external analysis. We propose a novel bronchoscope tool that would enable spatially dependent measurements of the functioning of the lungs by determining local concentrations of carbon dioxide, which will be produced by healthy parts of the lung at rates that are higher than from portions where gas exchange is impaired. The gas analyzer is based on a compact laser absorption spectrometer making use of fiber optics for delivery and return of low intensity diode laser radiation to and from the measurement chamber at the distal end of a flexible conduit. The appropriate optical wavelength was chosen such that light is selectively absorbed only by gaseous CO2. The optical absorption takes place over a short path (8.8 mm) within a rigid, 12 mm long, perforated probe tip. Wavelength modulation spectroscopy was adopted as the analytical technique to reduce the noise on the optical signal and yield measurements of relative CO2 concentration every 180 ms with a precision as low as 600 part-per-million by volume. The primary objective of such a device is to see if additional spatial information about the lungs functionality can be gathered, which will complement visual observation.